Editorial - Grenni, Héctor (Teoría y Praxis, 2022)
This issue of Teoría y Praxis has a special objective: to recall the document of the Second Latin American Episcopal Conference (CELAM), gathered in the city of Medellin, Colombia, in 1968: 50 years of that historic document, which we know simply as the 'document of Medellin'. The importance comes both from the historical context of those years, and of the significance of the document.